Quality of life on climacteric nursing professionals - Thamyres Campos Fonsêca; Mariana Nepomuceno Giron; Lina Márcia Miguéis Berardinelli; Lucia Helena Garcia Penna (Universidade Federal do Ceará, 2014)
The climacteric has some unique features, especially related to body function, where women experience changes of several orders in this period of life, then, it is important to study the quality of life of nursing professionals. It was proposed to analyze the impact of climacteric on the quality of life of nursing professionals who work directly with care. Through an exploratory, descriptive study developed with nine nursing professionals under climacteric in a University Hospital of Rio de Janeiro, in 2010, we proceeded to collect data through semi-structured interviews and the results were submitted to content analysis. All respondents experience changes in their quality of life after 35 years of age, at work, concerning eating, leisure activities, physical activities and other habits and lifestyles. It was concluded that climacteric affects the quality of life of nursing professionals in relationships, at work, concerning eating, physical activities, sleeping patterns and leisure.